Modeling of the Mechanism of Generating Processes of Water Electrolysis and Photosynthesis with Solar Energy Used for Productions of Gas Oxygen and Hydrogen, of Concentrate of the High-calorie Microalgae Chlorella, and for Industrial Wastewater Treatment - M. Shoikhedbrod (International Journal of Advance in Molecular Engineering, 2024)
The use of solar energy for generation of the process of water electrolysis, permitting the oxygen and hydrogen gases production, concentration of the high-calorie fast productive Chlorella microalgae, and industrial wastewater treatment is the most promising direction today. This is explained by the complete absence of electrical energy consumption for the implementation of these industrial technological projects. No less interesting is the process of photosynthesis of phytoplankton cells, which also allows, with the help of solar energy, to the phytoplankton cells of the world's oceans to utilize atmospheric carbon dioxide, reducing greenhouse gas emissions, and enrich it with oxygen. The main source of conversion of solar energy into electrical energy is a silicon semiconductor using strong special additives. The main source of conversion of solar energy into the biological activity of phytoplankton cells is the photosynthetic apparatus of phytoplankton cells - chlorophyll. The article presents molecular modeling of the mechanism of generation of the processes of water electrolysis and photosynthesis of microalgae cells by solar energy, permitting to carry out, developed by the author: the treatment of industrial wastewater; the concentration of high-calorie, fast-productive microalgae Chlorella; the production of gas oxygen and hydrogen.
Keywords: Solar Energy; conversion of solar energy into biological activity; conversion solar energy into electrical energy; electrolysis; oxygen and hydrogen gases production; photosynthesis